2014
DOI: 10.1055/s-0034-1372438
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Treatment Delay in Aneurysmal Subarachnoid Hemorrhage Patients

Abstract: Risk factors associated with treatment delay in aSAH patients include older age, nonwhite race, surgical clipping, and admission to low surgical volume hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
20
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 38 publications
1
20
1
Order By: Relevance
“…An increased availability of diagnostic imaging is also suggested to have a positive impact on the diagnosis of aSAH. [65,66] However, within rural and regional hospitals, this availability does not always include appropriate radiologist services with experience in interpreting cerebral imaging. [67] Physician led, rather than radiologist led, interpretation of imaging has previously been identified as a leading cause of diagnostic errors in emergency settings.…”
Section: Modifiable Health Risk Factorsmentioning
confidence: 99%
“…An increased availability of diagnostic imaging is also suggested to have a positive impact on the diagnosis of aSAH. [65,66] However, within rural and regional hospitals, this availability does not always include appropriate radiologist services with experience in interpreting cerebral imaging. [67] Physician led, rather than radiologist led, interpretation of imaging has previously been identified as a leading cause of diagnostic errors in emergency settings.…”
Section: Modifiable Health Risk Factorsmentioning
confidence: 99%
“…A number of recent studies have evaluated the aneurysm treatment experience at a nationwide level, noting factors resulting in procedural delays 9–11. Although studies have suggested that surgical clipping is associated with increased wait times when compared with aneurysm coiling, the specific factors associated with these delays have not yet been determined 10. We set out to evaluate time to clipping and time to coiling following SAH in a national cohort according to hospital and patient demographics.…”
Section: Introductionmentioning
confidence: 99%
“…Delayed treatment for aSAH appears to be common. In one study from a single hospital in Melbourne, only half the people with aSAH were treated within 24 hours of onset (Phillips et al, 2011) while in a country-wide study in the UK more than 60% were treated >2 days after onset of symptoms (Langham et al, 2009) and in the US 10-25% of people are treated at >48 hours after admission (Sarmiento et al, 2015;Siddiq et al, 2012). Our understanding of the causes of these delays remains limited, in turn affecting our ability to develop interventions targeted at reducing delays and improving outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…being female, older age, living in urban areas, having inter-facility transfer) had a bidirectional influence on time to treatment . Other potential predictors of delays in aSAH treatment include pre-hospital delays (Germans et al, 2014), admission on the weekend (Sarmiento et al, 2015;Siddiq et al, 2012), having pre-treatment complications (Sonig et al, 2018) or having surgical clipping (Sarmiento et al, 2015;Sonig et al, 2018).…”
Section: Introductionmentioning
confidence: 99%